2013
DOI: 10.1002/hep.26694
|View full text |Cite
|
Sign up to set email alerts
|

Human CD14+CTLA-4+regulatory dendritic cells suppress T-cell response by cytotoxic T-lymphocyte antigen-4-dependent IL-10 and indoleamine-2,3-dioxygenase production in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignancies worldwide with limited therapeutic options. HCC‐induced immunosuppression often leads to ineffectiveness of immuno‐promoting therapies. Currently, suppressing the suppressors has become the potential strategy for cancer immunotherapy. So, figuring out the immunosuppressive mechanisms induced and employed by HCC will be helpful to the design and application of HCC immunotherapy. Here, we identified one new subset of human CD14+CTLA‐4+ regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
141
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(151 citation statements)
references
References 42 publications
(89 reference statements)
2
141
1
1
Order By: Relevance
“…5 Recently, immune suppressive regulatory DCs have also been identified in HCC patients. 34 DCs differentiate into mature DCs through microenvironmental stimuli that can efficiently launch immune responses. Kerkar and colleagues found that IL-12 could reprogram immunosuppressive DCs to regain immunostimulating functions that promote anti-tumor T cells.…”
Section: Discussionmentioning
confidence: 99%
“…5 Recently, immune suppressive regulatory DCs have also been identified in HCC patients. 34 DCs differentiate into mature DCs through microenvironmental stimuli that can efficiently launch immune responses. Kerkar and colleagues found that IL-12 could reprogram immunosuppressive DCs to regain immunostimulating functions that promote anti-tumor T cells.…”
Section: Discussionmentioning
confidence: 99%
“…These regulatory DCs express high amounts of IL-10, nitric oxide (NO), VEGF and arginase I, and thus contribute to immune evasion by tumors [14]. In humans, regulatory DCs have been described as CD14 + CD11b high CTLA-4 + PD-1 + and represent less than 13% of peripheral bone marrow-derived cells in [15]. Human regulatory DCs have been reported to suppress T-cell activation not only through IL-10 but also indoleamine 2,3-dioxygenase (IDO) production [15].…”
Section: Rationally Combining Anti-vegf Therapy With Checkpoint Inhibmentioning
confidence: 99%
“…Recently, a new regulatory subset of DCs called CD14 + cytotoxic Tlymphocyteassociated protein (CTLA)4 + DCs, which expresses inhibitory molecule like CTLA4 and programmed death receptor (PD)1, were observed in the peripheral blood lymphocytes and tumor masses of HCC patients [16] . High levels of anti-inflammatory cytokine, IL-10, and indoleamine 2, 3dioxygenase secreted by these cells' poststimulation suppressed the CD4 + Tcell immune response, thereby assisting tumor progression and immune escape.…”
Section: Dendritic Cellsmentioning
confidence: 99%